Electrical storm refractory multiple antiarrhythmic medications was stopped by interatrial shunting procedure—A case report - Han, Caiping; Qiu, Rujie; Li, Lei; Han, Min; Xu, Chengyi; Liu, Li; Liu, Chengwei (Frontiers in Cardiovascular Medicine, 2022)
Electrical Storm (ES) remains a major dilemma for clinicians, often presenting as a medical emergency associated with significant adverse outcomes. The mechanisms behind triggering ES are complex. Although the increased activation of the sympathetic nervous system was widely accepted as a major mechanism in initiating and maintaining ES, it’s thought the interaction between mechanical and electrical substrates may play an important role in some situations. Here we present a case of ES that was refractory to multiple antiarrhythmic medications but was stopped by interatrial shunting. We aim to highlight the utility of this practice as an alternative therapeutic strategy for ES patients initially refractory to antiarrhythmic medications when there is evidence to indicate increased left ventricular filling pressure and left atrial pressure.